Greater Manila Area transtation development Makati Central Subway Station : a study on the design of common stations in the Greater Manila Area - Espina, Ira Christopher Jacob A. (College of Architecture, University of the Philippines Diliman, 2020)
Infrastructure is one of the keys to unlocking the potential of the Philippines as an emerging economy, and the Philippines is currently investing in the implementation of these projects, notably in the Greater Manila Area. Though the railway network is expanding, the connectivity of these railway lines, specially the creation of common stations should also be given due attention. The Makati Central Subway Station is a study of how common stations are to be designed in the context to the Greater Manila Area, as it is the common station between two flagship and pioneering subway projects in the Philippines, the Mega Manila Subway Project and the Makati Intra-City Subway Project. This study will attempt to apply the concept of a transtation, a play on the words, station, transfer, and transition, which a station that proposes to transition its users from their homes to their everyday work/school duties, both by physically transferring them the most efficient way possible, and mentally transferring their mindset from one of lethargy, from being at home, to one of energy sufficient for the working environment. This is done by applying the theory of Choice Architecture and Nudges in the design of the subway station.